ANALISIS KARAKTER INTEGRITAS PETUGAS PARKIR TERHADAP PELAKSANAAN PERATURAN DAERAH NOMOR 3 TAHUN 2010 TENTANG RETRIBUSI PELAYANAN PARKIR DI KAWASAN TUGU KERIS SIGINJAI KOTABARU KOTA JAMBI - Muhammad Refi Rajuspa; Priazki Hajri; Dona Sariani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the actualization of parking attendants' integrity characters in implementing Regional Regulation Number 3 of 2010 concerning Public Roadside Parking Service Retribution in the Tugu Keris Siginjai Area, Kotabaru, Jambi City, alongside the field obstacles encountered. The primary issue centers on the critical role of integrity in preventing Local Revenue (PAD) leakage and optimizing public service. This qualitative study utilizes a descriptive research design. Ten informants were selected via purposive sampling, consisting of four parking attendants as primary informants, five parking service users as key informants, and one representative from the Jambi City Transportation Agency as an additional informant. Data were gathered through passive participant observation, structured interviews, and documentation, then analyzed using an interactive model comprising data collection, data reduction, data display, and conclusion drawing. The results indicate that the actualization of parking attendants' integrity characters has been inconsistent, revealing a gap between normative regulations and moral action. While attendants understand official tariffs and strictly wear official vests, accountability in automatically distributing parking tickets remains very low. Violations persist as tariff inflation (Rp3,000 for motorcycles and Rp5,000–Rp10,000 for cars) occurs during peak hours, accompanied by poor vehicle management causing traffic and emotional control issues. The primary obstacles include external sociological challenges from local thugs (premanism), low financial welfare due to the absence of government salaries, and visitors paying below standard rates. Conversely, management is supported by cross-sectoral oversight from the Transportation Agency, the Saber Pungli Team, and periodic ticket audits.